2020
DOI: 10.1039/d0fo00267d
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of ellagic acid for endometriosis treatment: its effect on a human endometrial cell cycle, adhesion and migration

Abstract: EA treatment decreases cell adhesion and migration of endometrial cells and alters the progression of an endometrial stromal cell line cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…More specifically, the antioxidant and anti-inflammatory effects of the phenolic compounds extracted from Rubus idaeus leaves can be attributed to the rich composition of the extract in ellagic acid, quercetin, and kaempferol derivatives, as well as catechins. The effects of ellagic acid have been described to regulate multiple pathways such as proinflammatory agents’ inhibition [ 66 ], antioxidant response activation [ 67 ], fibrotic formation, growth factor, and adhesion molecules regulation [ 68 , 69 ]. Quercetin enacts an anti-inflammatory activity through the inhibition of the eicosanoid’s pathway via enzymatic and non-enzymatic arachidonic acid oxidation, which in turn can reduce the production of inflammatory mediators such as prostaglandins and leukotrienes [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the antioxidant and anti-inflammatory effects of the phenolic compounds extracted from Rubus idaeus leaves can be attributed to the rich composition of the extract in ellagic acid, quercetin, and kaempferol derivatives, as well as catechins. The effects of ellagic acid have been described to regulate multiple pathways such as proinflammatory agents’ inhibition [ 66 ], antioxidant response activation [ 67 ], fibrotic formation, growth factor, and adhesion molecules regulation [ 68 , 69 ]. Quercetin enacts an anti-inflammatory activity through the inhibition of the eicosanoid’s pathway via enzymatic and non-enzymatic arachidonic acid oxidation, which in turn can reduce the production of inflammatory mediators such as prostaglandins and leukotrienes [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…MC is the root bark of Paeonia suffruticosa Andr., and is widely used for activating blood circulation and resolving blood stasis (Bai et al, 2021;Chen et al, 2005); however, it has been rarely investigated in endometriosis. It has been reported that the main bioactive ingredients of MC include paeonol, gallic acid, quercetin, β-sitosterol, paeoniol, et al Previous reports showed that gallic acid reduced the adhesion and cell cycle progression of HESCs and provided a new and promising candidate for treating endometriosis (Mc Cormack et al, 2020). Quercetin could inhibit proliferation in VK2/E6E7 and End1/E6E7 cells to act as a natural therapeutic to reduce and treat endometriosis (Park et al, 2019).…”
Section: Discussionmentioning
confidence: 99%